UMBILICAL VEIN INJECTION OF 800 MICROGRAM MISOPROSTOL VERSUS OXYTOCIN IN THE MANAGEMENT OF RETAINED PLACENTA - Mahmood, Maryam Bakir; Shamdeen, Maida Y; Hamadmeen, Bafrin H. (Journal of Sulaimani Medical College, 2018)
Background The third stage of labor is timed from the delivery of the baby to the expulsion of the placenta and membranes. This normally takes five and fifteen minutes. It may be complicated with retained placenta. Consequently, intervention should be started promptly. Objectives We aimed to evaluate the effectiveness of umbilical vein injection of misoprostol (800 Microgram) versus oxytocin (20 units) for the treatment of retained placenta. Materials and Methods This is a double-blinded randomized clinical trial, conducted at the Maternity Teaching Hospital, Sulaimani, Kurdistan Region, Iraq, from October 1, 2016 to December 31, 2017. Fifty patients whom delivered vaginally and complicated by retained placenta were randomly allocated into two groups;group1 received 800 mcg of misoprostol (four Misotac® 200 mcg, Pfizer) and, group2 received 20 IU of oxytocin (NOVARTIS) each diluted in 20 ml of normal saline were infused through umbilical vein for the two groups respectively. The outcome was measured by using time interval of placental separation and amount of blood loss. Results The mean ± SD age was (30.5 ± 5.8) and (27.8 ± 5) for the oxytocin and misoprostol groups respectively. There were a statistically significant relationship between the type of drug injections and a statistically very highly significant difference between the type of drug injections and time interval for the placental separation (P-value of 0.04 and P-value of <0.001 respectively). There was also a statistical significant difference in the mean vaginal blood loss between the two groups (169.3 ± 88.1 ml, 150 ± 89.4 ml) in oxytocin and misoprostol groups respectively), (P-value = 0.03). Conclusions The intraumbilical vein injection of misoprostol was better than oxytocin for the reduction of time needed till placental separation and associated with less blood loss.
Keywords: Intraumbilical vein injection; Retained placenta; Misoprostol; Oxytocin